Influence of the Administrators’ Promotion Criteria on Teachers’ Satisfaction in Public Primary Schools in Bondo Sub-County, Kenya - Machogu Gladys Nyaera; Dr. Charles Ocharo Momanyi (IJRDO- Journal of Educational Research, 2020)
Teachers play a major role in the education in terms of imparting knowledge and skills to the learners. The purpose of this study is to establish the influence of the administrators’ promotion criteria on teachers’ satisfaction in public primary schools in Bondo Sub-County. The research methodology was mixed methods approach and concurrent triangulation design. The target population was 700 teachers and 300 administrators and random sampling technique was used to identify the participants, the researcher used the sample size of 150 teachers. Questionnaires and face-face interview was to be used to obtain data. The research tools were piloted in 5 schools to test their validity and reliability. The collected data was coded and edited for completeness before analysis. The study found out that the relationship between a teacher and a student is the fundamental point which determines a learner’s interest. Over and above this key bond, the school management should also try to cultivate a growing bond between them and students. The teachers are satisfied, students feel safe and take care, and the management takes the credit for a job well-done. It is important school head teachers to continually evaluate the performance of their teachers and encourage them to further their education. This will catapult them for promotion opportunities thus increasing the satisfaction of the teachers.